The disputes about the interpretation of "Amoris Laetitia" in the websites of catholic weekly days - Wojciech Klimski (Journal of Modern Science, 2023)
Objectives The subject of the article is the way of presenting the dispute caused by the exhortation of Pope Francis "Amoris Laetitia" on the websites of Catholic weeklies. This exhortation concerns the issues of marital morality and family life, and its fragments (concerning the rules of giving communion to divorced persons) were written ambiguously. So bishops and theologians have developed different interpretations of these principles. Since many of them were mutually exclusive, a dispute over the rules of administering communion to divorced persons (which still exists today) flared up among the leaders of the Catholic Church.